2009
DOI: 10.1038/bmt.2009.109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of general vs regional anaesthesia for BM harvesting: a retrospective study of anaesthesia-related complications

Abstract: This retrospective study was conducted to evaluate the safety and complications profile of general anaesthesia (GA) compared with that of regional anaesthesia (RA) for BM harvesting (BMH). The study included 281 donations carried out between 1992 and 1999. Of these, 204 (73%) were allogeneic donations, and GA was carried out in 69% (140 of 204) and RA in 31% (64 of 204) of cases. The other 77 donations were autologous (27%), using GA in 87% (67 of 77) and RA in 13% (10 of 77) of cases. No life-threatening comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…This strongly suggests that the choice of anaesthesia depends on the donor or the anaesthetist's preference. 18 Jobs involving mild to moderate daily work activities have been associated with fewer of days off work following BM donation compared with jobs involving more heavy duties. 17 Blood donors had more physical difficulty with donation; their previous experience with blood donation may have led them to underestimate the physical impact of BM donation.…”
Section: Full Blood Countmentioning
confidence: 99%
See 2 more Smart Citations
“…This strongly suggests that the choice of anaesthesia depends on the donor or the anaesthetist's preference. 18 Jobs involving mild to moderate daily work activities have been associated with fewer of days off work following BM donation compared with jobs involving more heavy duties. 17 Blood donors had more physical difficulty with donation; their previous experience with blood donation may have led them to underestimate the physical impact of BM donation.…”
Section: Full Blood Countmentioning
confidence: 99%
“…60 There are few reports that compare general versus regional anaesthesia for BM harvesting. 11,18,[61][62][63] Local anaesthesia has reduced risk of trauma, because the patient is awake and vigilant, whereas general anaesthesia may produce a minor respiratory risk, because the donor has a secured airway. 64 Most studies found no difference regarding numbers of adverse events during or after the procedure.…”
Section: Full Blood Countmentioning
confidence: 99%
See 1 more Smart Citation
“…o r g peripheral blood (PBSC) by apheresis [8]. BM harvest is performed under general or regional anesthesia [9], and stem cells are directly aspirated from both hip bones (posterior superior iliac crests). The complications of BM harvesting are well known and are usually mild and selflimiting.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most recently, a retrospective review of nearly 300 cases failed to demonstrate a clear advantage of regional anesthesia over general anesthesia for BM harvest, although satisfactory postoperative analgesia was not considered in that study and regional anesthesia was limited to subarachnoid block. 9 PVBs provide pre-emptive analgesia by blocking all sensory input, including sympathetic input from the surgical site prior to the injury. 10 They have been shown to reduce hospital stay, decrease postoperative nausea and vomiting, decrease blood loss and increase patient satisfaction.…”
mentioning
confidence: 99%